The Manhattan Cocktail : A Modern Guide to the Whiskey Classic - Schmid, Albert W. A. (Book collections on Project MUSE., 2015)
Alongside other classic cocktails such as the Old Fashioned, the Mint Julep, and the Martini, the Manhattan has been a staple of the sophisticated bar scene since the late nineteenth century. Never out of style, this iconic drink has seen a renaissance in the contemporary craft cocktail movement, its popularity boosted by TV's Mad Men. In theory, the recipe is simple: a mixture of whiskey, vermouth, and bitters stirred with ice, strained, and presented in a cocktail glass that is garnished with a cherry. But the exact ingredients and the proportions -- as well as the drink's true origins -- inspire great debate. This essential guide covers everything that the aficionado needs to know about the classic cocktail through an examination of its history and ingredients. Author Albert W.A. Schmid dispels several persistent myths, including the tale that the Manhattan was created in 1874 by bartenders at New York City's Manhattan Club to honor the newly elected Governor Samuel Jones Tilden at Lady Randolph Churchill's request. Schmid also explores the places and people that have contributed to the popularity of the drink and inspired its lore, including J.P. Morgan, who enjoyed a Manhattan every day at the end of trading on Wall Street. The Manhattan Cocktail also examines the effects of various bourbons and whiskeys on the aroma and flavor, even answering the age-old question of "shaken or stirred'" Featuring more than fifty recipes as well as notes and anecdotes from personalities as diverse as bartender and mixologist Dale DeGroff and writer Sir Kingsley Amis, this entertaining read will delight both the cocktail novice and the seasoned connoisseur